EAA/EMQN best practice guidelines for molecular diagnosis of Y‐chromosomal microdeletions: state‐of‐the‐art 2013. (January 2014) - Krausz, C.; Hoefsloot, L.; Simoni, M.; Tüttelmann, F.
Summary The molecular diagnosis of Y‐chromosomal microdeletions is a common routine genetic test which is part of the diagnostic workup of azoospermic and severe oligozoospermic men. Since 1999, the European Academy of Andrology (EAA) and the European Molecular Genetics Quality Network (EMQN) have been actively involved in supporting the improvement of the quality of the diagnostic assays by publication of the laboratory guidelines for molecular diagnosis of Y‐chromosomal microdeletions and by offering external quality assessment trials. The present revision of the 2004 laboratory guidelines summarizes all the clinical novelties related to the Y chromosome (classic, partial and gene‐specific deletions, genotype–phenotype correlations, methodological issues) and provides an update on the results of the quality control programme. These aspects also reflect the consensus of a large group of specialists present at a round table session during the recent Florence‐Utah‐Symposium on 'Genetics of male infertility' (Florence, 19–21 September, 2013). During the last 10 years the gr/gr deletion has been demonstrated as a significant risk factor for impaired sperm production. However, the screening for this deletion type in the routine diagnostic setting is still a debated issue among experts. The original basic protocol based on two multiplex polymerase chain reactions remains fully valid and appropriate for accurate diagnosis of complete AZF deletions and it requires only a minor modification in populations with a specific Y chromosome background. However, in light of novel data on genotype–phenotype correlations, the extension analysis for the AZFa and AZFb deletions is now routinely recommended. Novel methods and kits with excessively high number of markers do not improve the sensitivity of the test, may even complicate the interpretation of the results and are not recommended. Annual participation in an external quality control programme is strongly encouraged. The 12‐year experience with the EMQN/EAA scheme has shown a steep decline in diagnostic (genotyping) error rate and a simultaneous improvement on reporting practice.